PENGARUH LOYALITAS KARYAWAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PMP UNIT BOBBIN JEMBER - Izzatun Nisa’ Khaidar Albasari; Mei Retno Adiwati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to determine the effect of employee loyalty and work environment on employee performance at PT. PMP Bobbin Unit Jember. The data used is primary data used is primary data used is primary data from at PT.PMP Bobbin unit Jember. The data sample was taken using the purposive sampling method with the criteria of working period of more than equal to 20 years with a total of 78 samples that will be tested using the SEM PLS application, from the results of the analysis it is known that employee loyalty has an influence on employee performance, while the work environment variable is known to be less effect on employee performance at PT. PMP Bobbin unit Jember.